KARAKTERISTIK PENDERITA TIFUS ABDOMINALIS DENGAN PEMERIKSAAN TEST WIDAL RAWAT INAP DI RSU. Dr. F.L.TOBING SIBOLGA JANUARI 2010 - JULI 2012 - Alista Br Simanjuntak; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Typhus abdominalis is one of the communicable diseases related to the environment which do not up to standart of health. Based on WHO (2003) there are 17 million Typhus abdominalis cases with CFR of 3,5%. On 2010 at the F.L. Tobing Sibolga Hospital proportion Typhus abdominalis sufferer is 1,5%, on 2011 is 2,1% and 2012 as of July the proportion is 2,9%. The population in this research are 358 sufferer were taken by purposive random sampling with criteria have Widal Test laboratory are 181. For analyzing, it is used chi-square and t-test. The results obtained that the highest sociodemographic proportion are age 1-10 years old 59.1%, men 55.8%, 42.3% not attending school, not working 42.5%, unmarried 86.7%, and the city came Sibolga 58.6%.The highest proportion of Typhus abdominalis sufferer with 100% fever symptoms,89.5% without complications, 36.8% respiratory complications, average of length stay 3.73 days, 84.0% discharge with outpatient treatment, 54.1% not expense by self, O titer (=1/160) 54.7%, H titer (=1/320) 37.6%. There is no significant difference between the proportion of ages, sexes,the average treatment time, O titer, H titer based on the status of complications. There are significant differences between the average treatment time based on the source cost. There is no significant difference between coming home condition based sourcing costs.Expected to the hospital to give information to the people who have recovered for further examination once a month and maintain personal hygiene and the environment. Keywords: Typhus abdominalis, characteristics